Artificial intelligence in dental practice: a review - Prasannam, Reemitha P.; A. Arul Murugan, Priyanka; L. Narayanan, Rajesh; Jagadeson, Mahesh; S., Vishnu Prasad; K., Indrapriyadharshini (International Journal Of Community Medicine And Public Health, 2023)
The human brain is a distinctly complex structure with several interlinked neurons that transmit signals all over the body. The search for an excellent model mimicking the human mind has led to a sophisticated breakthrough in what's referred to as artificial intelligence (AI). AI methodologies have determined programs in numerous disciplines ranging from telecommunication, aerospace, robotics, medical analysis, alternate marketplace, law, science, or entertainment to name some. Medical clinical decision support system (CDSS), a factor of AI is being carried out in dentistry which includes Artificial neural networks (ANN), genetic algorithms (GA) and Fuzzy logic. Various fields of drugs such as diagnostic systems, biomedical analysis, image analysis, and drug development have utilized this complicated and tremendously advanced detail of AI. The AI systems along with virtual reality have been used now not handiest to lessen dental anxiety but also to appear as an effective tool for the non-pharmacological manipulation of pain. Ordinary, AI offers us a glimpse of the destiny tool to be able to assist dentists in an inconceivable manner.